Political Tv Talk Shows on Greek Television: Live Broadcasting as an ideological and Cognitive frame - Vovou, Ioanna (Brazilian journalism research, 2007)
This paper presents a semiopragmatic analysis of the political talk shows on Greek television that reveals a symbolic conception of the TV studio and it’s value-attributing mechanisms through which principles of democratic dialogue are enacted inside this kind of social and media frame. Political talk shows create the notion of a complex temporality, larger than the concept of events presented live, afecting the political and social vision of the audience.